Sử dụng một số thuật toán tìm chuỗi signature để phân tích và phát hiện xâm nhập trong hệ thống mạng. - Đặng, Lê Nam (Trường Đại học Đà Lạt, 2012)
Algorithm to find the best sequence in the study of searching patterns to apply network-attack identifications has been evolving constantly. In this article, we deployed the search algorithm by simulation the forms of network attacks on intrusion detection system combined with firewall, IDS/ IPS, as well as the usage of tools for network monitoring such as open-source tool munin to analyze the forms of attack. Accordingly, we measure the time of pattern identification in the Snort IDS/ IPS, and at the same time measure both the performance of Snort and the number of packets passing through Snort, the amount of alerts per second on Snort, the number of packet drops, bandwidth, throughtput, the size of average packets, etc. relying on intelligent algorithms built in Snort in order to offer a way to choose different algorithms for each different form of intrusion detection.